Komunikasi Kesehatan Penanganan Stunting Tahun 2022 di Puskesmas Menanga, Kecamatan Solor Timur, Nusa Tenggara Timur - Muhtadiah, Dian (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2023)
This research with the title Health Communication Menanga Health Center, East Solor District, East Nusa Tenggara in Handling Stunting Problems in 2022 was conducted with the aim of knowing the health communication patterns used by nutrisions (nutritionists) in handling malnutrition. This research is expected to be useful for handling malnutrition. The method used in this research is qualitative descriptive method. The data analysis used is domain analysis. Data were obtained using interviews, observation and documentation. The results of this study indicate that interpersonal premier communication is well implemented. The process of delivering messages carried out by nutritionists (nutritionists) with parents of stunted patients is applied successfully to improve malnutrition in stunted patients so that the number of stunted patients is reduced.